Cardiovascular and cerebrovascular risk with nonsteroidal anti-inflammatory drugs and cyclooxygenase 2 inhibitors: latest evidence and clinical implications. (June 2017) - Fanelli, Andrea; Ghisi, Daniela; Aprile, Pierangelo Lora; Lapi, Francesco
Observational studies and meta-analyses have shown that the administration of nonsteroidal anti-inflammatory drugs (NSAIDs), especially when prescribed at high doses for long periods of time, can potentially increase the risk of cardiovascular diseases. The increased thrombotic risk related to the use of NSAIDs is mainly due to their cyclooxygenase 2 selectivity. The dosage use, the formulation selected and the duration of the therapy are other factors that can significantly impact on the cardiovascular risk. In order to minimize the risk, prescription of the right drug based on the patient's features and the different safety profiles of several NSAIDs that are available on the market is key for their appropriate administration. Despite the baseline cardiovascular and gastrointestinal risk of each patient, monitoring of patients is suggested for increases in blood pressure, development of edema, deterioration of renal function, or gastrointestinal bleeding during long-term treatment with NSAIDs.